Accurate Wavelength Calibration Method for Spectrometer Using Low Coherence Interferometry - Kim, Ji-Hyun; Han, Jae-Ho; Jeong, Jichai (Journal of lightwave technology, 2015)
Dispersive spectrometers are subject to wavelength dispersion errors due to aberration, ruling errors, etc. Thus, their calibration forms an integral aspect of their usage. In this context, we present an interferometric wavelength calibration method for calibrating dispersive spectrometers. The calibration system is based on low coherence interferometry. By analyzing the sinusoidal interference patterns that are modulated in a spectrum, we determine the distribution of wavelengths in a spectrometer using the zero-crossing detection. The spectral sampling interval of the spectrometer is estimated by determining the sampling interval in the z-domain. Assigning only one wavelength to the corresponding camera pixel using a narrowband light source allows the determination of entire wavelengths accurately. We use the information of the wavelength distribution, spectral sampling interval, and wavelength data to achieve accurate calibration. Our experimental results show that the proposed method calibrates wavelength more accurately than conventional methods, since the interferometric calibration can reduce the wavelength fitting error arising from extrapolation. Moreover, the proposed calibration method can reduce the side-lobe amplitude maximally by 4.8 dB when applied to OCT imaging. We believe that our findings can significantly aid in the development of spectrometry.